2008
DOI: 10.1093/jn/138.1.60
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Growth Restriction Affects the Proteomes of the Small Intestine, Liver, and Skeletal Muscle in Newborn Pigs

Abstract: Efficiency of nutrient utilization is high in neonates with normal birth weights but is reduced in those with intrauterine growth restriction (IUGR). However, the underlying mechanisms are largely unknown. This study was conducted with the piglet model and proteomics technology to test the hypothesis that IUGR affects expression of key proteins that regulate growth and development of the small intestine, liver, and muscle, the major organs involved in the digestion, absorption, and metabolism of dietary nutrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
232
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 276 publications
(248 citation statements)
references
References 33 publications
11
232
2
3
Order By: Relevance
“…In a recent study of Wu and co-workers (Wang et al, 2008) where proteome differences in tissues of runt and normal pigs were investigated, it was suggested that runts might be subject to higher systemic oxidative stress. These conclusions were based on changes in the expression of hepatic and muscle peroxiredoxin-1, transferrin and ζ-crystallin, proteins which comprise several components of the complex cellular oxidative defense system (Wang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study of Wu and co-workers (Wang et al, 2008) where proteome differences in tissues of runt and normal pigs were investigated, it was suggested that runts might be subject to higher systemic oxidative stress. These conclusions were based on changes in the expression of hepatic and muscle peroxiredoxin-1, transferrin and ζ-crystallin, proteins which comprise several components of the complex cellular oxidative defense system (Wang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of Wu and co-workers (Wang et al, 2008) where proteome differences in tissues of runt and normal pigs were investigated, it was suggested that runts might be subject to higher systemic oxidative stress. These conclusions were based on changes in the expression of hepatic and muscle peroxiredoxin-1, transferrin and ζ-crystallin, proteins which comprise several components of the complex cellular oxidative defense system (Wang et al, 2008). If levels of circulating protein carbonyls are indeed an indication of overall oxidative stress and protein damage (Nyström, 2005) then the data presented here suggest that increased oxidative metabolism or sensitivity alone, cannot explain differences in growth performance in runt piglets.…”
Section: Discussionmentioning
confidence: 99%
“…et al, 2014b), liver , and skeletal muscle (Wang T. et al, 2013). Additionally, concentrations of key proteins involved in growth and development were reduced, while there was an abundance of proteins associated with oxidative stress, proteolysis, and ATP hydrolysis in the small intestine, liver, and muscle of low-birth-weight piglets (Wang et al, 2008). Impaired development and dysfunction of those organs and tissues that play vital roles in digestion, absorption, and metabolism of dietary nutrients (Jobgen et al, 2006) could permanently decrease postnatal growth performance and efficiency of nutrient utilization in piglets.…”
Section: Pre-weaning Growth Performancementioning
confidence: 97%
“…In neonatal pig, the small intestine was defined as the portion of the digestive tract between the pylorus and the ileocecal valve, with the first 10-cm segment being duodenum, and was divided into duodenum, jejunum, and ileum (Wang et al 2008). The jejunum was further divided into proximal and distal segments of equal length.…”
Section: Sample Collectionmentioning
confidence: 99%
“…In addition, it negatively affects the development and function of digestive tract (Wang et al 2005). Studies have shown that the expression levels of growth-related proteins (Wang et al 2005(Wang et al , 2008 and stress-responsible genes (Liu et al 2008) were severely affected by IUGR. However, little is known about the effect of IUGR on the expression and function of heat shock protein 70 (Hsp70) in intestine of infants and animals.…”
Section: Introductionmentioning
confidence: 99%